2012
DOI: 10.1177/0020764012440674
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of factors associated with social worker attitudes toward suicide

Abstract: Our findings suggest that suicide education should incorporate programmes directed at altering permissive attitudes toward suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 31 publications
5
28
2
1
Order By: Relevance
“…We found differences in effect size by type of profession for the ATTS subscales Suicidal Expression as Mere Threat, Common Occurrence, and Preventability/Readiness to Help. Previous studies have demonstrated that attitudes toward suicide differ according to professional background . Our findings also support previous research indicating that attitudes toward suicide are affected by the experience of participating in other suicide‐prevention training programs and by the experience of working with a suicidal patient or their family.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found differences in effect size by type of profession for the ATTS subscales Suicidal Expression as Mere Threat, Common Occurrence, and Preventability/Readiness to Help. Previous studies have demonstrated that attitudes toward suicide differ according to professional background . Our findings also support previous research indicating that attitudes toward suicide are affected by the experience of participating in other suicide‐prevention training programs and by the experience of working with a suicidal patient or their family.…”
Section: Discussionsupporting
confidence: 89%
“…This scale consists of 37 items scored on a 5‐point Likert scale ranging from 1 ( Strongly agree ) to 5 ( Strongly disagree ). We used a six‐factor model identified in a previous Japanese study; the factors were Right to Suicide, Suicidal Expression as Mere Threat, Impulsiveness, Common Occurrence, Unjustified Behavior, and Preventability/Readiness to Help. We interpreted higher scores on Right to Suicide, Suicidal Expression as Mere Threat, and Impulsiveness as indicating a more favorable attitude toward suicide (range: 1–5).…”
Section: Methodsmentioning
confidence: 99%
“…Of them, we chose ATTS to look for an appropriate scale measuring South Koreans’ attitudes towards suicide. A psychometric test of the Korean ATTS would be added to the evidence from a few studies regarding that of ATTS [ 10 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…We employed the Japanese version of the Attitudes Toward Suicide questionnaire (ATTS) to assess the attitudes toward suicide held by the study participants. 12 We employed a six factor model that was previously developed in studies of Japanese attitudes, including “right to suicide”, “common occurrence”, “suicidal expression as mere threat”, “unjustified behavior”, “preventability/readiness to help”, and “impulsiveness”. 12 , 13 Each item, with the exception of items 10 and 28, was scored on a five point scale from 1 (strongly agree) to 5 (strongly disagree).…”
Section: Methodsmentioning
confidence: 99%
“… 12 We employed a six factor model that was previously developed in studies of Japanese attitudes, including “right to suicide”, “common occurrence”, “suicidal expression as mere threat”, “unjustified behavior”, “preventability/readiness to help”, and “impulsiveness”. 12 , 13 Each item, with the exception of items 10 and 28, was scored on a five point scale from 1 (strongly agree) to 5 (strongly disagree). Items 10 and 28 were scored using a different scoring method that employed a five point scale from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Methodsmentioning
confidence: 99%